Musings on social cohesion in South Africa - Tredoux, Colin (PINS-Psychology in Society, 2023)
[BOOK REVIEW] Ballantine, Christopher, Chapman, Michael, Erwin, Kira & Maré, Gerhard (eds) (2017) (2015) Living together, living apart: Social cohesion in a future South Africa. Pietermaritzburg: UKZN Press. ISBN 978-1-86914-332-9 pbk. Pages vii + 197 This slim volume offers a set of short essays on a range of topics, loosely bound together by the subtitle of the book – the question of social cohesion in South Africa. What does the phrase “social cohesion” mean, though? The editors ask this question at the outset, and conclude that it seems like a social goal that cannot be argued against (who would argue that “social cohesion” is a bad thing for a society to have?). For that reason, and because it appears to mean so much in governmental and intellectual circles in South Africa, the editors offer us the reflections of a diverse array of scholars and authors. Philosophy, Linguistics, Literature, Music, Legal Studies, Sociology, Developmental Studies, Genetics, Urban Geography, and Physics, are some of the home disciplines of the authors who apply themselves to the question(s) at hand.